Utilization of Paperless Technology as Predictor of Staff Performance in Technical Colleges in Osun State, Nigeria - O. Oke, Jonathan; Oludele, Lydia Yemisi (Online Journal for TVET Practitioners, 2022)
In the recent past, paperless technologies are being adopted by many educational institutions, including the technical colleges, for e-learning and making learning more accessible to students. This study investigated how paperless technologies could predict the performance of staff of Technical Colleges in Osun State, Nigeria.  Two hundred and twenty (220) technical staff and thirty-six (36) administrative staff of the nine Government Technical Colleges in Osun State formed the population of the study out of which one hundred and fifty-four (154) technical and twenty-five (25) administrative staff were randomly selected. Two research questions guided the study while one hypothesis was tested at 0.05 alpha level.  Questionnaire was used for data collection while data collected based on the questionnaire were analyzed using simple mean statistical method. Hypothesis generated was tested using regression analysis with the aid of Statistical Packages for Social Sciences (SPSS). The study found that utilization of paperless technology significantly predicts staff performance.